Naturally Occurring HCV NS5A/B Inhibitor Resistance-Associated Mutations to Direct-Acting Antivirals. Issue 5 (July 2016) - ; Nguyen, Linh Thuy; Hall, Naomi; Sheerin, Dylan; Carr, Michael; De Gascun, Cillian F
Background: Direct-acting antivirals (DAAs) have significantly improved the treatment response in HCV chronic infection with higher potency and better tolerance. We established the prevalence of naturally occurring NS5A and NS5B inhibitor resistance-associated mutations (RAMs) in HCV genotype (GT)-1 chronically infected individuals in Ireland. Methods: In a multicentre cohort study, employing sequencing-based analysis, the presence of RAMs was determined in the HCV NS5A ( n =119) and the NS5B ( n =60). Results: Naturally occurring RAMs in NS5A (M28V, R30Q, L31I, P58S, E62D and Y93H) were identified in 14.3% (17/119) of cases. Notably, the major RAM Y93H was found in 15.2% (7/46) of GT-1b versus none (0/73) in GT-1a ( P =0.0009). The frequency of Y93H present in IFNL3 rs12979860 CC major homozygotes (30%, 3/10) was higher than in the non-CC group (11.1%, 4/36). GT-1b-infected individuals harbouring Y93H had significantly higher viral loads than those without this mutation ( P =0.006). Additionally, two novel insertions in GT-1a and GT-1b were identified in the NS5A interferon sensitivity-determining region. In NS5B, only minor pre-existing RAMs (L159F, C316N and I434M) were detected in 10% (6/60) of samples. The proportion of individuals harbouring multiple RAMs in different DAA target regions was low. Conclusions: RAMs to novel DAAs were infrequent in the DAA-naive population in the present study. The NS5A Y93H substitution was the only significant RAM identified. Given the low frequency of multiple RAMs in NS3, NS5A and NS5B regions and the unclear impact of preexisting Y93H on the response in combination therapies, the role of pre-treatment RAM analysis in treatment-naive individuals requires further investigation.